Desarrollo de reactivos caseros para el aprendizaje experimental de las ciencias naturales en los novenos años de educación básica paralelos A y C de la Unidad Educativa Isabel de Godin periodo Abril - Julio 2017 - Paredes Nuñez, Richar Renato (2017)
At the “Isabel de Godin” Educational Institution in the city of Riobamba, there are veryfew physical resource and didac materials to develop experimental activities in the Naturales Sciencies laboratory. For this reason, the development of homemade reagents for the experimental learning of the Natural Sciencie is proposed for which it is proposed as and objective to implement experimental activities using home reagents, for the experimental learning of the Natural Sciencies in the ninth year of basic education room “A” and “C” of the Educational Unit Isabel de Godin from April to Juliy 2017. Evereryday experimentation guarantees a prior knoelege, in whitch an anchor is made and thus make learning meaningful, when we do some of the practical activies with homemade materials, students can reproduce them in their homes. Thee applied methodology was not experimental and field, with bibliographical consultations that based the theoretical framework, and descriptive because the students were investigated the use of experimental activities and their aplplication in the learning of natural Sciences. For the collection of the information, structured surveys were used, applyning the simple to eigthty students. When analyzing the results it can be determined that a high index of students are in favor of the use of reagents extracted from the médium as an alternative to to develop experimental activities in the are of Natural Sciencicies. As conclosions it was determined that the use of home reagents favors the learning of the NATURAL Scieces because it allows to link the cognitive part procedural and attitudinal. Therefore it is recommended to apply a guide of home reagents for the experimental learning of natural Sciencie.